Rehabilitation Model of Drugs Victims Through Integrative Approach in Orphanage of Pondok Pesantren Ar-rahman Palembang - Akmal Hawi (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2019)
This study aims to: 1) reveal how the implementation of the rehabilitation process of integrative models for adolescent drug addicts; 2) explain the factors that hinder and support the integrative process of rehabilitation of adolescent drug addicts; and 3) explain the changes experienced by teenage drug addicts after undergoing an integrative rehabilitation process. This research is a qualitative research, using a phenomenological research model. The research subjects were nursing board and victim victims. In searching for data, methods of documentation, observation and in-depth interviews are used. While the technical analysis through the process of reduction, display and verification. The results of this study are; 1) the process of implementing the rehabilitation of adolescent drug addicts, carried out in an integrated manner between medicaltherapy, psychological and spiritual. 2) The central figure of the therapist is the ex-rehabilitation center's former addicts and alumni, so that they understand the problems faced by addicts who are nurtured and are very competent in guiding the healing process. 3) Inhibiting factors, namely: adolescents have emotional traits, cognitive damage, saturation, and lack of parental support. Supporting factors, namely: caregiver affection, discipline and government support. 4) Rehabilitation of drug addicts, has succeeded in reviving awareness not to use drugs, and led to changes in attitudes